The effect of different strains of Helicobacter pylori on platelet aggregation - Paul A Corcoran; John C Atherton; Steve W Kerrigan; Torkel Wadstrom; Frank E Murray; Richard M Peek; Desmond J Fitzgerald; Dermot M Cox; Michael F Byrne (Canadian Journal of Gastroenterology)
BACKGROUND AND AIMS: Helicobacter pylori is the major causative agent in peptic ulcer disease and is strongly implicated in the development of gastric cancer. It has also been linked, less strongly, to cardiovascular disease. The mechanisms by which certain strains of H pylori induce platelet aggregation through interactions with platelet glycoprotein Ib have been previously described.